The effect of colchicine on alveolar bone loss in ligature-induced periodontitis - TOKER,Hulya (2019)
Abstract Colchicine is widely used in the treatment of several inflammatory diseases due to its anti-inflammatory effect, but effects on bone metabolism are unclear. The aim of this study was to evaluate the effects of systemically-administered colchicine on healthy periodontium and experimentally-induced periodontitis. In total, 42 male Wistar rats were included in this study. A non-ligated group constituting the negative control group (Control, C, n = 6) and a ligature-only group forming the positive control group (LO, n = 12) were created separately. Twelve rats were treated with 0.4 mg/kg colchicine and another 12 with 1 mg/kg colchicine. In the colchicine-administered groups, right mandibles constituted the ligated groups (1 mgC-L or 0.4 mgC-L) and left mandibles formed the corresponding non-ligated controls (1mgC or 0.4mgC). Silk ligatures were placed at the gingival margin of the lower first molars. The animals were euthanized at different time-points of healing (11 or 30 days). Alveolar bone loss was clinically measured and TRAP+ osteoclasts, osteoblastic activity, and MMP-1 expression were examined histologically. There was no increase in alveolar bone loss with either colchicine dose in healthy periodontium (p > 0.05) and the highest level of alveolar bone loss, TRAP+ osteoclast number, and MMP-1 expression were measured in the LO group (p < 0.05). The 0.4 mgC-L group showed less alveolar bone loss at 11 days (p < 0.05), but greater loss at 30 days. The 1 mgC-L group showed higher osteoblast number than the other ligated groups (p < 0.05) at both time-points. In summary, colchicine did not increase alveolar bone loss in healthy periodontium and also may tend to reduce periodontitis progression. However, further extensive study is necessary to understand the mechanism of colchicine action on alveolar bone loss in periodontitis.